Primordial germ cells as a potential shared cell of origin for mucinous cystic neoplasms of the pancreas and mucinous ovarian tumors. Issue 4 (19th October 2018) - Elias, Kevin M; Tsantoulis, Petros; Tille, Jean‐Christophe; Vitonis, Allison; Doyle, Leona A; Hornick, Jason L; Kaya, Gurkan; Barnes, Laurent; Cramer, Daniel W; Puppa, Giacomo; Stuckelberger, Sarah; Hooda, Jagmohan; et al.
Abstract: Mucinous ovarian tumors (MOTs) morphologically and epidemiologically resemble mucinous cystic neoplasms (MCNs) of the pancreas, sharing a similar stroma and both occurring disproportionately among young females. Additionally, MOTs and MCNs share similar clinical characteristics and immunohistochemical phenotypes. Exome sequencing has revealed frequent recurrent mutations in KRAS and RNF43 in both MOTs and MCNs. The cell of origin for these tumors remains unclear, but MOTs sometimes arise in the context of mature cystic teratomas and other primordial germ cell (PGC) tumors. We undertook the present study to investigate whether non‐teratoma‐associated MOTs and MCNs share a common cell of origin. Comparisons of the gene expression profiles of MOTs [including both the mucinous borderline ovarian tumors (MBOTs) and invasive mucinous ovarian carcinomas (MOCs)], high‐grade serous ovarian carcinomas, ovarian surface epithelium, Fallopian tube epithelium, normal pancreatic tissue, pancreatic duct adenocarcinomas, MCNs, and single‐cell RNA‐sequencing of PGCs revealed that both MOTs and MCNs are more closely related to PGCs than to either eutopic epithelial tumors or normal epithelia. We hypothesize that MCNs may arise from PGCs that stopped in the dorsal pancreas during their descent to the gonads during early human embryogenesis, while MOTs arise from PGCs in the ovary. Together, these data suggest a common pathway for the development of MCNs and MOTs, and suggest that these tumors may be more properly classified as germ cell tumor variants. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.